Exponential growth model of weevil populations: a didactic experiment for undergraduate course of Population Ecology - Bomfim, Maria Eduarda de Jesus; Braz, Claudiane de Lima; Conceição, Vanderléia dos Santos; Dias, Nayara Oliveira; Dias, Francielen da Silva; Freitas, Elton dos Santos; Jesus, Paloma Regina Peixoto de; Jesus, Verônica Santos de; Dourado Junior, Roberto da Silva; Modesto, Vitor Castor; Oliveira, Joanna Karine Gomes de; Pereira, Tainara da Silva; et al. (Acta Scientiarum. Biological Sciences, 2024)
Exponential model for population growth (exponential model) is a foundation to evaluate population dynamics in Population Ecology field. Here, we used a didactic experiment to teach exponential model for an undergraduate course of Population Ecology. We built nine populations of weevils with three different initial population sizes: eight, 16, and 32 individuals with three replicates each. We provided equal food resource availability, and counted their population sizes weekly for 12 weeks. We estimated the intrinsic growth rate (i.e., r parameter), by trials and errors with an exponential model build in an Excel spreadsheet. The population growth rate (i.e., dN/dt parameter) was estimated using r values. Replicates with eight and 16 individuals reached the highest values of r and dN/dt, while replicates with 32 individuals reached the lowest values. Beyond of exponential model, two density dependency issues acting in populations were observed. First, in the lowest initial population sizes we observed the effect of demographic stochasticity acting in both r and dN/dt in one of the three populations. Second, we observed the intraspecific competition reducing r values in largest initial populations. Therefore, we highlight the importance of didactic experiment into learning exponential model in Population Ecology course, both for teaching and learning practices.